2016
DOI: 10.1080/03054985.2016.1195734
|View full text |Cite
|
Sign up to set email alerts
|

Supervising an international teaching practicum: building partnerships in postcolonial contexts

Abstract: Teaching practicum experiences, including those in international contexts, are based on partnerships between institutions and host schools, and the partnership between the pre-service teacher, the cooperating teacher and the university supervisor. This article explores the relationship between preservice teachers and cooperating teachers in an international practicum in the Solomon Islands. It considers the way the cooperating teachers were positioned within the partnership, and raises questions about the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…In the study by Gilliland (2015) where the American students did the ITP in Thailand, the mentors must find ways to assist the PSTs to overcome the language issues, culture, and expectations from the host schools. Also, as mentioned by Major & Santoro (2016), they stated that the genuine partnership with shared responsibility of practicum supervision in any developing country is steps to build a good relationship for peace and harmony as knowledge is shared and valued, and this promotes others to accept and respect the differences of the local contexts in teaching.…”
Section: Interpersonal Skills In Teaching Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Gilliland (2015) where the American students did the ITP in Thailand, the mentors must find ways to assist the PSTs to overcome the language issues, culture, and expectations from the host schools. Also, as mentioned by Major & Santoro (2016), they stated that the genuine partnership with shared responsibility of practicum supervision in any developing country is steps to build a good relationship for peace and harmony as knowledge is shared and valued, and this promotes others to accept and respect the differences of the local contexts in teaching.…”
Section: Interpersonal Skills In Teaching Sciencementioning
confidence: 99%
“…Furthermore, some studies also suggested that the opportunity to participate in the ITP could enhance more profound understandings of other cultures and traditions (Kabilan et al, 2017b;Kissock & Richardson, 2010), develop intercultural competence (Tambyah, 2019) and culturally responsive teaching practices (Kabilan, 2013). Also, this kind of international experience must be supported by the academic program that includes opportunities for students to participate in intercultural competence and diversity-related issues, as well as to reflect on attitudes and expectations dealing with these issues (Gilliland, 2015;Major & Santoro, 2016). Furthermore, Allen & Wright (2014) have described the significant research on the practicum of student teachers, examined its purpose and duration, and analyzed the tasks assigned that are useful for information to those who want to experience the ITP.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors highlight that students who participated in them were empowered by the experience and developed global and intercultural competence, along with a deeper understanding and appreciation of cultural differences (Smolcic and Katunich, 2017;Cushner and Mahon, 2002;Pence and Macgillivray, 2008;Cushner, 2007;Masel Walters et al, 2009;Willard-Holt, 2001). However, some scholars have also raised concerns about the outcomes of international teaching practice programmes (for example, Klein and Wikan, 2019;Major and Santoro, 2016;Parr and Chan, 2015;Vande Berg et al, 2012). These studies indicate that such programmes can foster neocolonial attitudes and strengthen stereotypes, and, further, might be seen as part of a new form of imperialism.…”
Section: Introductionmentioning
confidence: 99%
“…from the home institutions. With some notable exceptions (for example, Aamaas et al, 2019;Major and Santoro, 2016;Martin and Griffiths, 2014;Martin and Raja, 2013), the role and views of the partners from the Global South, such as cooperating teachers, principals and administrative personnel in the host country, are seldom the subjects of data collection and analysis. Thus, there is an extensive literature on international practicums and their outcomes from the view of the participants in the Global North, but less so from the perception of the partners that receive the students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation